The relationship between teacher stress and job satisfaction as moderated by coping - Woods, Seth; Sebastian, James; Herman, Keith C.; Huang, Francis L.; Reinke, Wendy M.; Thompson, Aaron M. (Psychology in the schools, 2023)
The present study investigated the relationship between teacher stress and job satisfaction, and examined the role of coping as a moderator. Based on the transactional and Coping‐Competence‐Context models of stress we expected that coping would serve as a protective factor in the relationship between teacher stress and their job satisfaction. Stress, coping, and satisfaction were measured using single‐item scales which are cost‐effective and practical instruments for measuring and monitoring teacher stress. A total of 2347 teachers from 93 schools formed the sample for this study. Regression analysis with job satisfaction as the outcome, and stress, coping, and their interaction entered separately were used to test the primary hypothesis. Results showed that there was a negative correlation between stress and job satisfaction, and coping had a significant moderating effect. Increasing levels of stress had less of a negative impact on job satisfaction for teachers with high coping ratings compared to those with average or low coping ratings. Overall, our results suggest that the development of coping skills could be beneficial for mitigating the effects of stress on job satisfaction. Practitioner Points 1.Coping is a statistically significant moderator between stress and satisfaction. 2.As stress increases, those with high coping see smaller drops in satisfaction. 3.Conducted using single‐item measures, making it easy for practitioners to utilize.